The social brain and its development - Blakemore, Sarah-Jayne (Henry Stewart Talks, 2010)
Adolescence, Autism spectrum conditions, Development, MPFC, Prefrontal cortex, Puberty, Social cognition, Social brain, Theory of mind
Reviewed at 2022/04/12